Karakteristik dan Potensi Pangan Fungsional Snack Bar Berbasis Sorgum dengan Perbedaan Jenis Binder - Lewerissa, Karina; Mawarno, Binardo Adi Seno (Jurnal Teknologi dan Industri Pangan, 2024)
Currently, sorghum has been considered an important local food crop and specifically developed by the Ministry of Agriculture with the aims to support national food security. There are five centers for cultivating and processing sorghum-based products in Central Java. Besides ease of cultivation and versatility of its plant parts, sorghum has complete nutrition and potential as a functional food because it contains dietary fiber, antioxidants, and low glycemic index. This research investigated the quality of sorghum-based functional snack bars, including physical parameters (hardness) and sensory charactersitics (taste, aroma, color, texture, and acceptability). A Completely Randomized Design (CRD) was used to find the best formulation with different low-sugar binders (egg white, dark chocolate, and arenga sugar). The most satisfied formulation was further tested for nutritional content and functional food potential (dietary fiber, antioxidant activity, and total phenols). Statistical analysis using one-way ANOVA with Duncan and Kruskal-Wallis tests. The results showed that the sorghum snack bars incorporated with egg white was the best with a water content of 1.89% wb, protein 15.09% wb, fat 2.90% wb, carbohydrate 69% wb and total calories per 100 g product of 362.6 kcal. In terms of functional activity, it had a total dietary fiber of 8.2% wb and antioxidant activity by DPPH (2,2-diphynyl-1-picylhydrazyl) method of 57.69%. Overall, the nutrition content of the sorghum snack bar is comparable to the commercial ones and shows functional properties. Moreover, it also complies with quality requirement of granola snack bars according to the USDA.